Multichannel ECG and Noise Modeling: Application to Maternal and Fetal ECG Signals. (16th January 2007) - Sameni Sameni, Reza Reza; Clifford Clifford, Gari D. Gari D.; Jutten Jutten, Christian Christian; Shamsollahi Shamsollahi, Mohammad B. Mohammad B.
Abstract : A three-dimensional dynamic model of the electrical activity of the heart is presented. The model is based on the single dipole model of the heart and is later related to the body surface potentials through a linear model which accounts for the temporal movements and rotations of the cardiac dipole, together with a realistic ECG noise model. The proposed model is also generalized to maternal and fetal ECG mixtures recorded from the abdomen of pregnant women in single and multiple pregnancies. The applicability of the model for the evaluation of signal processing algorithms is illustrated using independent component analysis. Considering the difficulties and limitations of recording long-term ECG data, especially from pregnant women, the model described in this paper may serve as an effective means of simulation and analysis of a wide range of ECGs, including adults and fetuses.